Utilization of Betel Leaf Extract as a Natural Hand Sanitizer to Prevent The Spread of Covid-19 in MTS. S Al-Hidayah, Silo Baru Village, Asahan Regency - Syafitriani; Novianti; Andayani; Widyasari, Rina; Husein, Ismail (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Betel leaf (Piper betle Linn) can be found in Silo Baru Village, Silau Laut District, Asahan Regency. This service activity aims to increase public knowledge about the content of betel leaf extract compounds as natural hand sanitizers, improve community skills in processing traditional betel leaf plants, and produce environmentally friendly hand sanitizer products made from betel leaf. Betel leaf, known as a natural antiseptic, analgesic and anti-inflammatory. Betel leaf extract contains flavonoid compounds, polyphenols, tannins and essential oils that can eradicate disease-causing germs. The content of compounds in betel leaf extract 15% and above is as effective as 70% ethanol which can reduce the number of bacteria and viruses. This activity is carried out using mentoring and training methods. The results of this activity include producing a natural hand sanitizer product that can support government programs in preventing the spread of the covid-19 virus, increasing local community knowledge through students and several teachers at MTs.S Al-Hidayah who participate in mentoring on how to manage and the introduction of the content of betel leaf extract to be used as the main ingredient in making natural hand sanitizers.